# Calculator search results

Formula
Solve the equation
Graph
$x = 0.2 \left ( y - 3 \right )$
$x = 0.6 y - 1$
$x$-intercept
$\left ( - \dfrac { 3 } { 5 } , 0 \right )$
$y$-intercept
$\left ( 0 , 3 \right )$
$x$-intercept
$\left ( - 1 , 0 \right )$
$y$-intercept
$\left ( 0 , \dfrac { 5 } { 3 } \right )$
$0.2 \left( y-3 \right) = 0.6y-1$
$y = 1$
 Solve a solution to $y$
$\color{#FF6800}{ 0.2 } \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 0.6 y - 1$
 Multiply each term in parentheses by $0.2$
$\color{#FF6800}{ 0.2 } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 0.2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 0.6 y - 1$
$\color{#FF6800}{ 0.2 } \color{#FF6800}{ y } + 0.2 \times \left ( - 3 \right ) = 0.6 y - 1$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { y } { 5 } } + 0.2 \times \left ( - 3 \right ) = 0.6 y - 1$
$\dfrac { y } { 5 } + \color{#FF6800}{ 0.2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 0.6 y - 1$
 Multiply $0.2$ and $- 3$
$\dfrac { y } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ 0.6 } = 0.6 y - 1$
$\dfrac { y } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ 0.6 } = 0.6 y - 1$
 Convert decimals to fractions 
$\dfrac { y } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 5 } } = 0.6 y - 1$
$\dfrac { y } { 5 } - \dfrac { 3 } { 5 } = \color{#FF6800}{ 0.6 } \color{#FF6800}{ y } - 1$
 Calculate the multiplication expression 
$\dfrac { y } { 5 } - \dfrac { 3 } { 5 } = \color{#FF6800}{ \dfrac { 3 y } { 5 } } - 1$
$\color{#FF6800}{ \dfrac { y } { 5 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 5 } } = \color{#FF6800}{ \dfrac { 3 y } { 5 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \color{#FF6800}{ 3 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 }$
$\color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \color{#FF6800}{ 3 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 }$
 Organize the expression 
$\color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ y } = - 5 + 3$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } = - 5 + 3$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ 2 }$
 Divide both sides by the same number 
$\color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
 그래프 보기 
Graph
Solution search results